2017
DOI: 10.1038/s41598-017-16313-5
|View full text |Cite
|
Sign up to set email alerts
|

The electron-phonon interaction at deep Bi 2 Te3-semiconductor interfaces from Brillouin light scattering

Abstract: It is shown that the electron-phonon interaction at a conducting interface between a topological insulator thin film and a semiconductor substrate can be directly probed by means of high-resolution Brillouin light scattering (BLS). The observation of Kohn anomalies in the surface phonon dispersion curves of a 50 nm thick Bi2Te3 film on GaAs, besides demonstrating important electron-phonon coupling effects in the GHz frequency domain, shows that information on deep interface electrons can be obtained by tuning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 67 publications
0
9
1
Order By: Relevance
“…It is interesting to note that this value is similar to the ratio v RW /v SV = 0.83 which would be obtained for the (001) surface of a cubic crystal with the same elastic constant ratios C 12 /C 44 = 0.795 and C 11 /C 44 = 2.24 of Bi 2 Te 3 (see 56 ). Moreover, v RW from the present study is somewhat smaller than that recently measured with Brillouin scattering in Bi 2 Te 3 thin films grown on a stiffer substrate and with the RW penetration depths comparable to the film thickness 61 .…”
Section: Resultscontrasting
confidence: 78%
“…It is interesting to note that this value is similar to the ratio v RW /v SV = 0.83 which would be obtained for the (001) surface of a cubic crystal with the same elastic constant ratios C 12 /C 44 = 0.795 and C 11 /C 44 = 2.24 of Bi 2 Te 3 (see 56 ). Moreover, v RW from the present study is somewhat smaller than that recently measured with Brillouin scattering in Bi 2 Te 3 thin films grown on a stiffer substrate and with the RW penetration depths comparable to the film thickness 61 .…”
Section: Resultscontrasting
confidence: 78%
“…Tellurium is a semiconductor with a high thermoelectric gure of merit comparable to GeSi, 1 BiSb 2 or other well-known materials. [3][4][5] The chiral tellurium has been investigated for its anisotropic lattice thermal conductivity and p-type transport properties from anisotropic hole pockets of the Fermi surface. 6,7 In addition, very recently, structures with few-layers of tellurium were studied as two-dimensional topological materials.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, for sufficiently thin TI layers (between 3 QL’s and 9 QL’s), topologically protected surface states appear 30 and only surface phonons remain. The electron-surface AP coupling 18 can lead to spin-like oscillations of electrons, which can be exploited in device applications. Here, we demonstrated that not only thickness reduction leads to the symmetry breaking, but also LSP generation and interactions of the TI with different substrates.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of the interface and charge carrier properties can then be studied using light scattering spectroscopy 17 . Similarly, surface acoustic phonons have been recently employed as a “sonar” probe of electron-phonon coupling at the interface of Bi 2 Te 3 and GaAs 18 .…”
Section: Introductionmentioning
confidence: 99%